Postural adjustments of shoulder girdle and ankle joint in post-stroke subjects submitted to a physiotherapy intervention. A case series study - Conde, Ana Catarina Magalhães (2021)
Upper limb dysfunction is frequente in post-stroke subjects. Standing reach, need the modulation of global postural adjustments (PA), as shoulder girdle and ankle joint for daily life activities. Describe the PA behavior in time line between -800 milliseconds (ms) to +50 ms aftermovement onset, through the variation os muscle activity of superior trapezius (ST), inferior trapezius (IT), latissimus dorsi (LD), pectoralis major (PM), tibialis anterior (TA) and soleus (SOL), during standing reach in post-stroke subjects submitted to a physiotherapy intervention. Three participants with a history of stroke in the middle cerebral artery territory. The evaluated was done before intervention (MO) and after intervention (M1) in laboratory and clinical context. The muscle activity variation of muscles studied was collected using electromyography, in the scapular and sigittal plane. The time variation occur mostly in APA’s time window. In standing reach when ST, IT, Ld, PM, TA and SOL muscle varied its activity, was observed na activation behavior, bilaterally, in both moments. Except in ipsilesional LD at MO, in case B. In this study was observed a variation of muscle activity of shoulder girdle and ankle joint, in post-stroke subjects submitted to a physiotherapy intervention.